2013
DOI: 10.1007/s13577-013-0080-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal cell differentiation of mesenchymal stem cells originating from canine amniotic fluid

Abstract: The amniotic fluid contains mesenchymal stem cells (MSCs) and can be readily available for tissue engineering. Regenerative treatments such as tissue engineering, cell therapy, and transplantation show potential in clinical trials of degenerative diseases. Disease presentation and clinical responses in the Canis familiaris not only are physiologically similar to human compared with other traditional mammalian models but is also a suitable model for human diseases. The aim of this study was to investigate wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…In the present study, the expressions of the neural stem cell marker Nestin as well as the neural precursor markers βIII-tubulin and NCAM were detected in canine OS cells. In previous studies [23,24,34] , these markers were also found in mesenchymal stem cells which were consistent with our findings. On the otherhand, we could not determine the GFAP mRNA expression in stem cells consisted with results of the study of Chung et al [24] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the expressions of the neural stem cell marker Nestin as well as the neural precursor markers βIII-tubulin and NCAM were detected in canine OS cells. In previous studies [23,24,34] , these markers were also found in mesenchymal stem cells which were consistent with our findings. On the otherhand, we could not determine the GFAP mRNA expression in stem cells consisted with results of the study of Chung et al [24] .…”
Section: Discussionsupporting
confidence: 93%
“…The importance of the dog, being as a large animal model of human neurodegenerative diseases, has led to interest in the isolation and characterization of dog stem cells derived from various tissues such as adipose, bone marrow and amnion [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…44,74,75 Canine MSCs naturally express some of the neural markers 76 and show neuronal differentiation potentiality when isolated from various sources such as adipose tissue, 77 amniotic fluid, 78 and bone marrow. 79 CNTs have been studied as culture substrates to support neuron growth and differentiation basically due to their electrical conductivity as well as their nanotopographical feature creating tight contacts with neuron membranes, leading to electrical shortcuts.…”
Section: Das Et Almentioning
confidence: 99%
“…Then many studies demonstrated that neural cells derived from bone marrow MSCs expressed mRNA species encoding many type of genes such as β-tubulin III (an early neural marker), nestin, neurofilaments (NFs), glial fibrillary acidic protein (GFAP) (as neural cell markers), and the specific neural markers such as choline acetyltransferase (ChAT), and MAP-2 and many other markers [22] [42] [44]- [46].…”
Section: Discussionmentioning
confidence: 99%